2023
DOI: 10.1098/rsos.220819
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of Piper chaudocanum stem extract mediated silver nanoparticles for colorimetric detection of Hg 2+ ions and antibacterial activity

Abstract: A green synthetic approach to synthesize silver nanoparticles (AgNPs) using the stem extract of Piper chaudocanum for highly sensitive colorimetric detection of Hg 2+ with a low limit of detection of 23 nM and easy colorimetric read-out has been reported. In addition, the biosynthesized AgNPs demonstrated efficient antibacterial activity against Escherichia coli , Pseudomonas aeruginosa and Staphylococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…However, in the case that the P. chaudocanum L. extract was added into the Zn (II) solution before the addition of the alkaline hydroxide solution, an interaction between the Zn (II) ions and the P. chaudocanum L. extract would occur, which was reflected by a reduction in the XRD diffraction peak intensity and an increase in the diffraction peak width of ZPS samples versus ZSP samples. The research [23] reported that the P. chaudocanum L. extract contained a wide range of substances, including alkaloids, triterpenoids, flavonoids, steroids, tannins, phenolic compounds, and piperine, an amide alkaloid that was considered to be a key component [23]. This suggested the formation of a complex between Zn (II) ions and the P. chaudocanum L. in the case of the ZPS samples, which are explained by the Equations ( 4) and ( 5) below:…”
Section: Phase Structure and Atom Composition Of Synthesized Zno Samplesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, in the case that the P. chaudocanum L. extract was added into the Zn (II) solution before the addition of the alkaline hydroxide solution, an interaction between the Zn (II) ions and the P. chaudocanum L. extract would occur, which was reflected by a reduction in the XRD diffraction peak intensity and an increase in the diffraction peak width of ZPS samples versus ZSP samples. The research [23] reported that the P. chaudocanum L. extract contained a wide range of substances, including alkaloids, triterpenoids, flavonoids, steroids, tannins, phenolic compounds, and piperine, an amide alkaloid that was considered to be a key component [23]. This suggested the formation of a complex between Zn (II) ions and the P. chaudocanum L. in the case of the ZPS samples, which are explained by the Equations ( 4) and ( 5) below:…”
Section: Phase Structure and Atom Composition Of Synthesized Zno Samplesmentioning
confidence: 99%
“…Several Piper species, such as P. longum [20], P. betle [21], and P. nigrum [22] have been employed as reducing and capping agents in the production of ZnO NPs. Recently, P. chaudocanum L., a member of the Piper genus, has been in employment to synthesize nanoparticles [23][24][25][26] because it comprises various compounds such as alkaloids, triterpenoids, flavonoids, steroids, tannins, phenolic compounds, and piperine. This amide alkaloid is considered to be a chief constituent [23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Piper chaudocanum (P.) belongs to the Piper genus, which has well known for the treatment of headache, hot liver, body aches, epilepsy in children, colds and u to cure all kinds of poisons and weather diseases. Piper chaudocanum consists of compounds, including alkaloids, triterpenoids, avonoids, steroids, tannins and phenolic compounds and piperine, an amide alkaloid such as a major compound [25]. Many plants belonging to the Piper genus such as P. longum [26], P. betle [27] and P. nigrum [28] were used as reducing and capping agents in the biosynthesis of ZnO NPs for application in anticancer and antibacterial.…”
Section: Introductionmentioning
confidence: 99%